Gasochromic response of Pd/NiO nanostructured film towards hydrogen. - Yaacob, Mohd. Hanif; Campbell, J.L.; Wisitsoraat, A.; Wlodarski, W. (American Scientific Publishers, 2011)
The gasochromic performance of nanostructured nickel oxide (NiO) films coated with 25 Å catalytic palladium (Pd) layer were investigated for low concentration hydrogen (H 2) sensing. NiO nanostructures of 20-30 nm sizes were produced via RF sputtering deposition of NiO x on quartz substrates and subsequently annealed at 500 °C. It was found that the Pd/NiO films show significant gasochromic response when exposed to H 2 at elevated temperatures. Integrating the absorbance change over a range of visible wavelengths (500-800 nm), has enabled very low concentrations of H 2 (0.06%) to be sensed in real time. T 90% response of 25 Å Pd/100 nm NiO film towards 0.06% H 2 in a balance of synthetic air was approximately 120 s at 170 °C. Similar H 2 concentration can be recovered in as little as 240 s at 170 °C.